Approaches to Identify Typical Mistakes by Primary Schoolchildren Studying Natural Science Concepts - Egorenko T.A.; Sanina S.P. (Психолого-педагогические исследования)
The article describes approaches to the typology of the main mistakes of primary schoolchildren studying natural science concepts. This is the overview of the problem of the development of natural science concepts in the works of native and foreign researchers. In the course of the analytical study, a comparison was made of the content, structure of tasks and methods of assessing the monitoring studies, as well as a comparison of descriptions of typical mistakes of primary school children. In “VPR” (“Vserossiiskie proverochnie raboti” are the obligatory Russian tests for schoolchildren), all subject knowledge is presented through certain skills, and the mistakes that chidlren make are interpreted as "gaps" in knowledge and skills that need to be filled. SAM (Student Achievement's Monitoring) reveals the "structure" of achievements and backlogs. SAM evaluation tool has proven itself well in assessing the natural science literacy of younger schoolchildren, namely the ability to act according to a model, the ability to act with understanding and the degree of freedom (the manifestation of natural science literacy) in the possession of certain modes of action. TIMSS (Trends in Mathematics and Science Study) aims to evaluate three parameters: "knowledge", "application" and "reasoning". Along with the correct answers of the children, their incorrect reasonings are also recorded. The analytical study showed no unified approach to the assessment of typical mistakes in the development of natural science concepts existing today. One of the promising directions can be the arrangement of a unified typology of the main mistakes of primary schoolchildren when studying natural science concepts and creation of an assessment tool based on it.